Improvement business process model and notation on the drink distribution industries using six core element - Khoirunnisa, Oktaria; Pertiwi, Dwika Ananda Agustina; Dianti, Erika Noor; Fattah, Ahmad Maulana Malik; Budiman, Kholiq (SHM Publisher, 2021)
The development of distribution and market segmentation has become the company's background in improving business processes. The purpose of this research is to analyze the business processes of beverage companies using Business Process Management (BPM) modeling and improvised based on six core element management. In the analysis process, it is found that there is no stock forecasting system in forecasting sales stock that must be fulfilled. The results of the study show that the Business Process Management model is improved with the addition of a stock forecasting system, so that business processes become more controlled with the presence of a product stock inventory forecasting system in the company.